2019
DOI: 10.1016/j.engstruct.2019.01.076
|View full text |Cite
|
Sign up to set email alerts
|

Arching in concrete slabs strengthened with near surface mounted fibre reinforced polymers

Abstract: This paper outlines basalt fibre reinforced polymer (BFRP) and carbon fibre reinforced polymer (CFRP) strengthening of laterally restrained concrete floor slabs. In-plane restraint has previously been shown to enhance slab capacity due to the development of internal compressive membrane action (CMA), which is not generally included in codified strength assessments. By installing fibre reinforced polymers (FRPs) using the near surface mounted (NSM) technique, disturbance to the existing structure can be minimis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Alkali-resistant glass fiber, as a material with high monofilament tensile strength, high elastic modulus, alkali resistance, corrosion resistance, and impact resistance, has a wide range of applications in the field of construction engineering, mainly used in non-load-bearing cement components [10]. It can be used as an auxiliary rib material to enhance the performance of concrete, and an appropriate amount of it can effectively improve the toughness of cement matrix [11]. The study by Yue et al [10,12,13] showed that blast furnace slag can be used as a raw material to prepare alkali-resistant glass fibers, and they found that it was a method to recycle waste materials, which improved the value of both, while protecting the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Alkali-resistant glass fiber, as a material with high monofilament tensile strength, high elastic modulus, alkali resistance, corrosion resistance, and impact resistance, has a wide range of applications in the field of construction engineering, mainly used in non-load-bearing cement components [10]. It can be used as an auxiliary rib material to enhance the performance of concrete, and an appropriate amount of it can effectively improve the toughness of cement matrix [11]. The study by Yue et al [10,12,13] showed that blast furnace slag can be used as a raw material to prepare alkali-resistant glass fibers, and they found that it was a method to recycle waste materials, which improved the value of both, while protecting the environment.…”
Section: Introductionmentioning
confidence: 99%